Angola Systematic Country Diagnostic : Creating Assets for the Poor - World Bank Group (World Bank, Washington, DC, 2019)
Angola is endowed with significant natural wealth, but it will need to better manage these resources and reinvest them into other forms of capital to establish a sustainable development path. Before independence, the country was a relatively advanced economy with diverse exports, although its population suffered under exploitative colonial rule. Decades of conflict, during the fight for independence and the civil war that followed, exacted a heavy toll on the population, infrastructure, and the economy. The end of the war in 2002 and a booming oil industry resulted in strong economic growth, but the poor saw very little benefit from this economic prosperity. The dependence on oil exports has created macroeconomic instability, and Angola has suffered periods of fiscal contraction due to fluctuations in commodity prices. Although the country has enjoyed strong gross domestic product (GDP) growth, this has been achieved by depleting natural capital for consumption, rather than reinvestment in other types of capital to generate sustainable growth. The recent change in leadership represents a window of opportunity for political and economic reform that will allow Angola to put itself on a path toward sustainable development.The Systematic Country Diagnostic (SCD) for Angola identifies pathways and priorities to eradicate poverty and boost shared prosperity by 2030. After providing the historical context of Angola, the SCD applies the concept of the “Changing Wealth of Nations” and identifies four binding constraints for Angola to reach the World Bank’s twin goals. Oil dependency in conjunction with a low global oil price creates macroeconomic and fiscal imbalances, constraining sustainable growth and poverty reduction in Angola. A weak private sector is unable to provide a sustained growth momentum, further constraining growth and poverty reduction. The poor remain excluded from growth, limiting realized growth, but more importantly, manifesting high poverty levels. Finally, weak governance is a cross-sectoral binding constraint contributing to unsatisfactory policy outcomes. The SCD ranks areas of intervention for each binding constraint and selects the top 10 priorities to overcome the binding constraints. With a new government in place, Angola is at a critical juncture to pursue a sustainable development path to reach poverty eradication and shared prosperity.